Padrão espectral de cultivares de soja por meio de perfis temporais do índice de vegetação por diferença normalizada (NDVI) - Lima, Paulo Henrique Peruzzo de (2014)
The economic importance of the soy culture demands the development of techniques that allow monitoring the development conditions of large-scale cultures. In this context crop monitoring by remote sensing is a tool with great potential. This monitoring is accomplished by vegetation indices, being commonly used the Normalized Difference Vegetation Index - NDVI. The temporal profiles of NDVI indicate the temporal evolution of biomass, which enables to monitor the phenological development, the duration of growth period, the vegetative peak, the physiological changes of leaves, and the periods of culture senescence. Thus, the aim of this study was analyzing the relations of the spectral response of soybean cultivars with their phenological development by NDVI. To accomplish this, two experiments were carried out within the Cooperativa Central de Pesquisa Agrícola - COODETEC, in Cascavel, in the state of Paraná. To study plants growth habits and different development cycles, five soy cultivars were used. Furthermore, two irrigation regimes were also tested: the normal one (N), in which there was no water stress, and the water stress regimen (CEH). For experiment 1, NDVI data was collected, while for experiment 2, NDVI and Leaf Area Index (LAI) data were collected. These elements were analyzed by comparative charts of the temporal evolution of NDVI profiles for cultivars, considering treatments N and CEH. The mean ratios were compared using the t-student test at the 5% significance level. The relation between NDVI of each cultivar with their respective phenological development stage was also established. For experiment 2, models of simple linear regression were generated between NDVI and LAI for each cultivar and irrigation condition. For experiment 1, the temporal profile of NDVI described the normal behavior of the culture in the first days after sowing (DAS), and it showed values close to 0.2; as the plants developed, the NDVI values increased until the maximum value, close to 0.9. Determinate cycle cultivars obtained maximum NDVI at 56 DAS and V7 stage, while cultivars of indeterminate cycle obtained NDVI maximum at 70 DAS and V8 stage. In general, normal water regime treatments showed higher NDVI than water stress treatments. Regarding the experiment 2, coefficients of determination from 0.50 to 0.86 were found. The NDVI was efficient in monitoring soybean culture development. Thus, functions set between NDVI and LAI can be used for monitoring the crop.